Aninha e outras vozes: a construção discursiva do sujeito em Vintém de Cobre, de Cora Coralina - Morais, Mara Rúbia de Souza Rodrigues (2006)
The general objective of this paper founded on the French discourse analysis is to investigate the discursive construction of the subject in the texts of Vintém de cobre: Meias confissões de Aninha , by Cora Coralina. Taking as central presupposition the subject s heterogeneous, dispersal and divided character, this discursive study proposes itself to analyse the several voices that cross Vintém de Cobre , producing the effect of subject s unit constructed, discursively, between the subject, itself, and its constitutive other. In this sense and from the category of enunciative heterogeneities (AUTHIER REVUZ, 1990) it analyses the functioning of two thematic trajectories (The past as privation and The redemption by the work) that in the ambit of sayings about childhood, sexuality and work, cut out for this study, compose the imaginary unit of the subject of this literary enunciation. Considering that this discursive subject is produced in the language relation with the conflicting context of patrimonization of the city of Goiás, the refering thematic trajectories operate discursive memory knowledges and inscribe meaning effects towards a dismystification of the past of people from Vila Boa (beneficial to a minority) and of work praise (given by the tourism and undertaken by everybody and to everybody). From the analysis of the discursive functioning of determined sequences that act as marker units of these thematic routes, this descriptive-analitic- interpretative research ratifies the hypothesis that, in Vintém de Cobre , the discursive memorialistic manifestation produces a subjectivity identified to what we can call discursive memorialistic formation of Goiás. In the same direction signs that this constituted subject in the process of identification with the knowledge of this discursive formation assumes, predominately, a favorable position to the patrimonization of Goiás Velho and to the adaptation of the city to the new reality created by this process of monumentalization. However, in the face of the interdiscourse plurality, that occurs in the discursive thread of Vintém de cobre , this paper stress that the constitutive saying of the subject in this discursive materiality oscilates between confront and alliance relations, established with the knowledges that are representative of other discursive formations. Therefore, signs the occurrence of lacks in the process of ideologic interpolation of the subject that presents, itself , therefore, necessarily marked by contradiction. As signs of the contradictory character of the subject in Vintém de Cobre , this study recognizes, beside discourses that derive to a dismystification of a past (beneficial only to some ones) and to the work affirmation (coming from the touristic exploration and undertaken by everybody and to everybody) the emergence of sayings that, in this discourse, end up converging senses to the maintenance of the socioeconomic order of Goiás past, guided by the work exploration and in strong power relations. In the path of representative elements of the discursive heterogeneity effects about the subject constitution it is reaffirmed in this paper, that the saying coherence and the subject produced by it in Vintém de Cobre is situated in the imaginary order. An order that shelters the necessary counterpart to an effect of subject s totality, as it resists to a perfect ideologic interpellation and assumes, predominantly (but not exclusively), a given position.